Cost Structure and Profit Stability: A Comparative Study between CMC- Kamal Textile Mills Ltd. and Square Textile Ltd.: and : A Comparative Study between CMC- and - Ahamed, Md. Jafaur (Asian Accounting and Auditing Advancement, 2011)
The cost structure is an important concept to be aware of and to be understood by all the concerned persons in any manufacturing or service providing organization conducting any economic activity and with an aim to improve quality of service as well as increasing productivity and profitability. In this study, an attempt has been made to compare the cost structure and show the impact of cost structure on profit stability between CMC-Kamal textile mills ltd. and Square textile ltd. The study reveals that CMC-Kamal textile mills ltd. enjoys wider movement in net income as changes take place in sales, with greater profit in business good years and greater losses in business bad years. On the other hand, Square textile mills ltd. enjoys somewhat greater stability in net income i.e. Square textile ltd. is less vulnerable to downturns than CMC-Kamal textile mills ltd., but it will do so at the risk of losing substantial profits if sales trend upwards in the long run. Researchers also found, due to consisting of lower fixed cost, square textile ltd. has a lower break-even point and a higher margin of safety; therefore, it will reach the profit as quickly as CMC-Kamal textile mills ltd. in the periods of sharply declining sales. The study also highlights the problems regarding cost structure and suggests how to overcome these problems. JEL Classification Code: D61, P52, L67, M49